Understanding the Conceptual of Geography Information System (GIS) for Project Management in Malaysian Construction Industry - Rashid, Fahira Ardina; Che Haron, Roziha (Research in Management of Technology and Business, 2024)
The construction industry in Malaysia is becoming more complex due to the current revolution of technology. To keep up with these changes, key players in the industry must upgrade their skills to align with the advancements of Industry Revolution 4.0.  One potential solution is the utilization of Geographic Information Systems (GIS), which facilitate smooth project management by analyzing and storing spatial data. However, Malaysia's construction sector has been found slow to adopt digital skills due to high cost, complexity, safety concerns, and cultural factors. This research aims to provide preliminary studies on GIS, including its benefits and potential applications in construction. Additionally, it explores the barriers to the adoption of GIS technology in the Malaysian construction industry. Furthermore, this study seeks to serve as a valuable resource for future researchers interested in exploring the role of GIS in construction.